Temperature dependent critical stress for {101¯2} twinning in magnesium micropillars at cryogenic temperatures. (15th March 2023) - della Ventura, Nicolò M.; Tian, Chunhua; Sharma, Amit; Edwards, Thomas E.J.; Schwiedrzik, J. Jakob; Logé, Roland E.; Michler, Johann; Maeder, Xavier
Abstract: Single-crystal magnesium micropillars (5 µm diameter) have been fabricated using focused ion beam (FIB) milling and loaded in compression along the [ 2 1 ¯ 1 ¯ 0 ] direction at cryogenic temperature ( T  = 184 K) at three different strain rates: 10 -4, 5 × 10 -3 and 10 -1 s -1 . The stress-strain curves and post-mortem analyses reveal the predominance of { 10 1 ¯ 2 } twinning. The critical stress required for twinning is detected to be significantly higher compared with that previously reported at higher temperatures for the same strain rates. From the experimental data, the temperature dependence of the strain rate sensitivity and activation volume for twinning is unveiled and observed to be constant and linearly dependent with T, respectively. By considering the activation energy ( Q ) in terms of stress-dependent dislocation motion using the rate equation proposed by Schoeck, for { 10 1 ¯ 2 } twinning, Q is determined to be 174 kJ mol -1 for T  < 273 K and 72 kJ mol -1 above. Graphical abstract: Image, graphical abstract